Towards standardisation of naming novel prokaryotic taxa in the age of high-throughput microbiology - Hildebrand, Falk; Pallen, Mark J.; Bork, Peer (Gut, 2020)
We thank Professor Oren for his interest in our work and for his constructive comments.1 In our recent article in Gut , we described the discovery of a new species that rose to high abundance in the human gut after treatment with ceftriaxone.2 We made the decision to propose taxonomic Latin names for this new species and for associated taxa because we wished to create a memorable, user-friendly, sustainable and transferable nomenclature that could be readily adopted by other researchers. Our proposals included the taxonomic hierarchy: UComantemales ord. nov., UComantemaea fam. nov., U Borkfalki gen. nov, U Borkfalki ceftriaxensis sp. nov. - - We adopted the superscript ‘U’ (for ‘uncultured’) prefix in line with a recent suggestion3 but accept that use of Candidatus has priority. However, in our defence, it is worth noting that recommendations for use of Candidatus cited by Professor Oren state that ‘this category …